Green Tea Catechin Epigallocatechin Gallate Inhibits Vegetative Cell Outgrowth and Expression of Beta-Lactamase Genes in Penicillin-Resistant Bacillus anthracis Strain PCr - Okutani, Akiko; Morikawa, Shigeru; Maeda, Ken (Pathogens, 2024)
The green tea catechin epigallocatechin gallate (EGCg) has antimicrobial effects on many bacteria. In this study, we investigated the inhibitory effects of EGCg on Bacillus anthracis spores and vegetative cells. The B. anthracis spores were insensitive to EGCg, but the growth of vegetative cells derived from germinated spores was inhibited by EGCg. Moreover, EGCg decreased the minimum inhibitory concentration of penicillin and meropenem for penicillin-resistant B. anthracis. In the penicillin-resistant B. anthracis strain, the transcription levels of the beta-lactamase genes (bla1 and bla2) decreased significantly following the treatment with 50 µg/mL EGCg. These results suggest that the appropriate application of EGCg may effectively control the penicillin-resistant B. anthracis growth and beta-lactamase production.